PYROELECTRIC PROPERTIES OF LEAD ZIRCONIUM TITANATE (PbZr0.525Ti0.475O3) METAL-FERROELECTRIC-METAL CAPACITOR AND ITS APPLICATION FOR IR SENSOR - M. Hikam; Irzaman Irzaman; H. DarmasetiawanArifin; P. Arifin; M. Budiman; M. Barmawi (Jurnal Sains Materi Indonesia, 2005)
PYROELECTRIC PROPERTIES OF LEAD ZIRCONIUM TITANATE (PbZr0.525Ti0.475O3) METAL-FERROELECTRIC-METAL CAPACITOR AND ITS APPLICATION FOR IR SENSOR. Thin films lead zirconium titanate (PbZr0.525Ti0.475O3) prepared on Pt(200)/SiO2/Si(100) substrates using chemical solution deposition (CSD) method for 0.5 M solution have been investigated. The films were grown by spin coating at 2500, 3000, 3500 rpm for 30 seconds, and then annealing at 750oC for 3 hours. X-ray diffraction (XRD), pyroelectric properties observation were employed to characterize the grown films. The film shows tetragonal structure with lattice constants are a = b = 4.141 Å, c = 3.828 Å. The voltage responsivity (rv) measured at chopper frequency of 2000 Hz and at wavelength of 947 nm are between 32.7-44.9 μV/W. Meanwhile, the pyroelectric coefficient (p) are in the range of 5.01 x 10-4-6.88 x 10-4 C/m2K for PZT thin films. These results show that PZT thin films are suitable for use as a pyroelectric IR sensor.